Photocatalytic Degradation of Chlorophenols on Tio 2-325mesh and Tio 2-P25. an Extended Kinetic Study of Photodegradation Under Competitive Conditions - Encina-Rojas, M; Pino-Lopez, E (2012)
The photodegradation kinetics UV/TiO 2-mediated of 4-chlorophenol (4-CP) and 2,6-dichlorophenol (2,6-DCP) mixtures were analyzed and compared under the same experimental conditions with both individual chlorophenols. The aim of this study was to get a more realistic approach to the critical processes involved in the photoinduced heterogeneous catalysis of systems containing more than one contaminant in competitive conditions, and also evaluate the influence of the particle size using the commercial TiO 2-325mesh and TiO 2-P25 as catalysts. The determination of the equilibrium adsorption constants in dark showed that the adsorption of the 2,6-DCP is considerably higher with respect to the 4-CP in both TiO 2 particles, but this relation decreases in the mixture of these pollutants. Several parameters influencing the reaction rate were studied including initial phenol concentration, catalyst loading, pH change, and particle size distribution. The degradation kinetics of individual phenols at low conversion showed a similar reactivity towards photogenerate hydroxyl radicals. In agreement with the reduced adsorption in the mixture, degradation rate of phenols was markedly lower in the mixture than that observed for the individual compounds. On the other hand, the photodegradation rate was higher on the TiO 2-325mesh than on TiO 2-P25, this is opposite to surface area of these particles indicating that other surface properties as pore size play an important role. The photoinduced degradation of these chlorophenols showed two main intermediate products that correspond to the degradation of each individual chlorophenols. © 2012 Elsevier B.V.